'All the places we were not supposed to go': a case study of formative class and gender habitus in adventure climbing. Issue 8 (16th November 2016) - Holland-Smith, David
Abstract : This paper explores the origins of meaning in adventurous activities. Specifically, the paper reports on a study of 10 adventure climbers in the Scottish mountaineering community. The study explores how formative experiences have influenced engagement in adventure climbing. Work has been done on the phenomenology of adventure and how individuals interpret and find meaning in the activity—this paper goes a step further and asks where do these dispositions come from? Using Bourdieu's ideas of field, habitus and forms of capital to frame these experiences in the wider social environment, early experiences are identified that, for the subjects of this study, provide a framework for their later adoption of the 'adventure habitus '. Among these influences are mainstream education, adventure education in particular, as well as broader formative experiences relating to factors such as gender and class. In addition, the study suggests that accounts differ between males and females in terms of their attitudes and dispositions towards adventure. This may relate to their respective experiences as well as expanding opportunities for both males and females. However, while the 'adventure field ' provides a context where women can develop transformative identities, these are nearly always subject to male validation.